Тowards validating qos requirements using stakeholder assessments of simulated service qualities - Шеховцов, В.А. (Eastern-European Journal of Enterprise Technologies, 2010)
We introduce an approach for validating quality of service (QoS) requirements (exemplified by performance and reliability requirements) by comparing them to interactive assessments of simulated service qualities by business stakeholders.